In the Name of Sovereignty. Right-Wing Populism and the Power of the Judiciary in Western Europe - Oscar Mazzoleni (Coordinamento SIBA, 2020)
This contribution addresses the question of how radical right-wing populist parties in Western Europe frame the issue of judicial power. To date, there have been very few in-depth empirical analyses on the topic – a gap that this article aims to fill. The paper will compare two radical right-wing populist parties, the Dutch Freedom Party and the Swiss People's Party, by focusing on party manifestos, parliamentary proceedings and public speeches by their leaders. Our findings show that these parties and leaders tend to undermine the rule of law by calling the impartial position of judges and the autonomy of the judiciary into question in the name of a popular, national and political sovereignism.